2013
DOI: 10.1002/star.201200194
|View full text |Cite
|
Sign up to set email alerts
|

Amylase inhibitors and their biomedical applications

Abstract: Amylases are a class of enzymes that hydrolyze starch to yield low molecular weight dextrins and sugars and they play important role in the digestion of carbohydrates. Inhibition of α‐amylase along with α‐glucosidase can significantly reduce the post‐prandial increase of blood glucose and can be an important strategy in the control of blood glucose level in the type‐2 diabetic patients. Hence, pancreatic α‐amylase and gastric glucoamylases are the major therapeutic targets for the type‐2 diabetes mellitus. Amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 82 publications
0
27
0
Order By: Relevance
“…Amylase inhibitors are also positioned as drugs for weight loss (Mahmood, 2016). Despite the use of such inhibitors in diabetes (Jayaraj et al, 2013), long term use warrants safe agents. To expand the drug repertoire by improving weak inhibitors, like those obtained from microbial products (metabolites), mimicry would be applicable.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Amylase inhibitors are also positioned as drugs for weight loss (Mahmood, 2016). Despite the use of such inhibitors in diabetes (Jayaraj et al, 2013), long term use warrants safe agents. To expand the drug repertoire by improving weak inhibitors, like those obtained from microbial products (metabolites), mimicry would be applicable.…”
Section: Downloaded Frommentioning
confidence: 99%
“…A number of enzyme inhibitors for different industrial applications have been isolated from microorganisms. Amylase inhibitors (starch blockers) prevent absorption of dietary starches by the body and are useful to control and treatment of carbohydrate dependent diseases, such as diabetes, obesity and hyperlipemia (Jayaraj et al 2013). In addition, the amylase inhibitors have also been reported for the treatment of rumen acidosis (Banks et al 2001).…”
Section: Other Therapeutic Agentsmentioning
confidence: 99%
“…Physical, chemical and enzymatic pre‐treatments of (plant) materials containing α‐glucans and on α‐glucans directly, to make them resist digestion (as found for example in forms of ‘resistant starch’) Digestive enzyme inhibitors (do not want full inhibition usually) as discussed for example elsewhere Glucose transporter inhibitors/blockers …”
Section: General – α‐Glucan Hydrolysis By Enzymesmentioning
confidence: 99%
“…Molecules that inhibit α‐amylase enzymes have been discussed in detail by Jayaraj et al de Sales et al discussed the structure of human salivary and pancreatic α‐amylase specifically and how plant extracts might inhibit these enzymes at the molecular level (with associated specific hydrogen bonding mechanisms). Wong and Huang suggested that both salivary and pancreatic α‐amylase could be inhibited by tea extracts; however they only showed evidence for the salivary enzyme being inhibited.…”
Section: General – α‐Glucan Hydrolysis By Enzymesmentioning
confidence: 99%